Promoting academic literacy with technology: successful laptop programs in K-12 schools - Warschauer, Mark; Grant, David; Real, Gabriel Del; Rousseau, Michele (System, 2004)
One of the main challenges that US schools face in educating English language learners is developing their academic literacy. This paper presents case studies of two K-12 schools that successfully employ high-technology environments, including laptop computers for each student, toward the development of English language learners’ academic language proficiency and academic literacy. In the first school, Latino fourth-grade students use laptops and other new technologies for a wide variety of pre- and post-reading tasks as part of their effort to transition from learning to read to reading to learn. In the second school, diverse immigrant and refugee students at the middle school level combine technology use with Expeditionary Learning to carry out community projects leading to the development of sophisticated products. In both schools, technology is used to engage students in cognitively demanding activity, motivate independent reading, and provide scaffolding for language development, while the researchers also made use of technology to document learning processes and outcomes. Taken together, the schools offer valuable lessons for utilization of technology to promote academic literacy among culturally and linguistically diverse students.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.system.2004.09.010 10/ffr68w 2339240:CR5JUUTC 2405685:9TQ7P4IC
Keywords: Laptops; Literacy; Technology

Sustainability and interactive radio instruction: why some projects last - Bosch, Andrea (Adapting Technology for School Improvement A Global Perspective, 2004)
This book presents a compilation of articles based on the premise that the move to advanced technology use in primary and secondary schools offers great hope for improving the access, quality, and efficiency of basic education. The aim of the book is to identify and examine how information technologies can be, and are being, used to strengthen the quality of primary and secondary education. The articles take a global focus, drawing on examples from a wide range of countries. The book analyzes the challenges that teachers and educational planners face as they make this move, and shares how those challenges are being met in some of the countries now engaged in this effort. Several major themes are explored: the role of technology in school improvement, top-down versus bottom-up approaches, interactive radio instruction in schools, computers in the classroom, technology in teacher education, and adopting and implementing technology. The conclusions of the book examine strategies such as the cross-national sharing of curriculum development and instructional materials, and the training and support of teachers and administrators. The need for new partnerships, such as public-private and central-local, to make continued developments in technology sustainable, are also examined. The book divides into 14 chapters: (1) The Role of Technology in School Improvement (David W. Chapman, Amy Garrett, and Lars O. Mahlck); (2) Are New Technologies Better Technologies? For Whom? (Claudio de Moura Castro); (3) International Uses of Education Technology Threats and Opportunities (Stephen P. Heyneman and Katherine Taylor Haynes); (4) Using Instructional Technology as a Bridge to the Future: Palau's Story (Gregory C. Sales and Masa-Aki N. Emesiochl); (5) The Introduction of Computers in Secondary Schools in Jamaica: A Case of Bottom-Up Reform (Errol Miller); (6) Distance Education in Ethiopia (Teshome Nekatibeb and Thomas Tilson); (7) Sustainability and Interactive Radio Instruction: Why Some Projects Last (Andrea Bosch); (8) Is Constructivism Universal? In Search of Meaningful Technology in Morocco and Namibia (Jeffrey Coupe, Jeffrey Goveia, Houcine El Haichour, and Alfred Ilukena); (9) Technology and Educational Change at the Local Level: The Case of the Campana Schools Network in Argentina (Cecilia Braslavsky and Laura Fumagalli); (10) The Pedagogical Uses of Web-Based Chat: The Brazilian Experience (Vera Atsuko Suguri, Maria de Lourdes Matos, Noara M. de Resende e Castro, Rosal va Ieda V. Guimaraes de Castro, Lurdes Marilene da Silva Jung, and Eric Rusten); (11) Utilizing Technology in a Rural Teacher Certification Programme in Iceland (Ingolfur Asgeir Johannesson and Anna Thora Baldursdottir); (12) Integrating Technology into Education: The Czech Approach (Bozena Mannova); (13) The School Online Initiative in German Schools: Empirical Results and Recommendations to Improve School Development (Renate Schulz-Zander); and (14) Effective Use of Technology to Improve Education: Lessons for Planners (Lars O. Mahlck and David W. Chapman). This book is intended for educational policymakers, administrators, planners, and curriculum development specialists concerned with how technology can be used to extend access and raise the quality of education in their countries. It is also intended for international organizations, development assistance agencies and NGOs that are often most responsible for advocating the use of technology as a solution to education problems in low and middle-income countries. (Individual chapters contain references.).
OCLC: 1064923325 KerkoCite.ItemAlsoKnownAs: 2339240:83PCK5YZ 2405685:KKI68BXJ
Keywords: Commitment; Cost; content